THE CONTROVERSY OVER SAMPRADAYA AND THE DYNAMICS OF HINDU INSTITUTION: CONTESTATION OF HINDU ELITES IN PALANGKA RAYA CITY - Adi, Agung; Suastra, I Made; Yudha Triguna, Ida Bagus Gde; Pujaastawa, Ida Bagus Gde (E-Journal of Cultural Studies, 2023)
This article is intended to analyze the controversy over sampradaya and the dynamics of Hindu institutions in general and ‘The Indonesia Administrative Council of Hindu Dharma’ Parisada Hindu Dharma Indonesia (PHDI) in particular in Palangka Raya City. The existence of sampradaya , as a transnational organization, has triggered an internal contestation among the Hindu elites. Being a qualitative study, this current study applies the approach of cultural studies, and emphasizes the different ways of interpreting one phenomenon. The data were obtained from the informants purposively chosen; therefore, they are categorized as the primary data source. The secondary data were obtained from the online and offline books available in the library, documents, articles and research results. The data were analyzed interactively in which Milles and Huberman were referred to. The data analysis includes the data reduction, the data presentation, the conclusion withdrawal or the data verification and interpretation. The results and discussion show that the controversy and contestation more dominantly result from the impact of globalization indicated by the dialectic process of affecting each other between the particularity referring to the symbols of the Bali Hindu identity, as one of the Hindu identities in Indonesia which is obliged to be maintained, and the universality, as the Hindu identity referring to the Indian culture, whose followers have spread all over the world. Keywords: sampradaya , PHDI, elite, Bali Hindu